(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2012)
Evaluate the playground areas, playground equipment and the access of children to recreation in the city of Hortolândia-SP. Descriptive and interpretative study. Based on the land occupation map of the city of Hortolândia-SP (2009-2012), we made an assessment of thirty areas that encompass their recreation system for observation in locus. It is clear that although there are areas, most of them are not available to children. The study revealed a problem of Public Policy regarding the access of children to recreation, taking into consideration their characteristics and mobility.